ADVANCES IN EXPERIMENTAL TECHNOLOGY BY THE EUROGAM DETECTOR SYSTEM - Kossionides, S. (HNPS Advances in Nuclear Physics, 2020)
For the high resolution gamma ray detector array EUROGAM new data acquisition solutions are being developed. Large volume high purity Ge detectors, with new shapes for increased efficiency, have been proposed and prototypes are now being tested. High resolution analog and digital electronics will be integrated within the VXIbus system to be used as the front end instrumentation bus. Also, distributed processing solutions are adopted in order to cope with the high data rates.